2023
DOI: 10.3390/jcm12072659
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Sacubitril-Valsartan on Cardiac Remodeling: A Parallel Echocardiographic Study of Left and Right Heart Adaptive Response

Abstract: Sacubitril/Valsartan (S/V) carries potential anti-remodeling properties, however long-term effects and biventricular adaptive response are poorly described. 76 HFrEF patients who underwent progressive uptitration of S/V, completed the annual scheduled follow-up. After a median follow-up of 11 (8–13) months, left ventricular (LV) reverse remodeling (RR) is defined as (1) absolute increase in LV ejection fraction (EF) ≥ 10% or LVEF ≥ 50% at follow-up and (2) decrease in indexed LV end-diastolic diameter (LVEDDi)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In the past few years, several studies reported sacubitril/valsartan could ameliorate HF by reversing ventricular remodeling in animal models (14)(15)(16)(17), from which we can postulate that sacubitril/ valsartan might play a role in attenuating the process of ventricular remodeling in HF children. Moreover, it is reported that sacubitril/valsartan might attenuate right ventricular modeling and benefit patients with right heart overload or dysfunction (18)(19)(20)(21), which is also proved in animal models in the latest researches (22).…”
Section: Discussionmentioning
confidence: 92%
“…In the past few years, several studies reported sacubitril/valsartan could ameliorate HF by reversing ventricular remodeling in animal models (14)(15)(16)(17), from which we can postulate that sacubitril/ valsartan might play a role in attenuating the process of ventricular remodeling in HF children. Moreover, it is reported that sacubitril/valsartan might attenuate right ventricular modeling and benefit patients with right heart overload or dysfunction (18)(19)(20)(21), which is also proved in animal models in the latest researches (22).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, both left and right ventricular dimensions and function modifications correlate with prognosis [ 29 , 30 ] and response to therapies [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and duration of HF are factors that can influence outcome. The increase in LVEF is more important in patients with non-ischemic or new-onset HF (≤12 months) [ 103 , 104 ]. In an early and reversible stage of the disease, sacubitril/valsartan can prevent global cardiac remodeling, and this was sustained by the results of the PIONEER-HF trial (Comparison of Sacubitril/Valsartan Versus Enalapril on Effect on NT-proBNP in Patients Stabilized From an Acute Heart Failure Episode) [ 105 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Furthermore, an important decrease in NT-proBNP level is associated with greater improvements in the LVEF and a more important reduction of LV volumes [ 102 ]. Additionally, a younger age and a sinus rhythm identify a subgroup of patients with a more likely reverse LV remodeling [ 104 ]. All of these features that are associated with reverse remodeling were present in our patient.…”
Section: Case Presentationmentioning
confidence: 99%